Sequence diversity of the Rh blood group system in Basques. (December 2018) - Flores-Bello, André; Mas-Ponte, David; Rosu, Miruna; Bosch, Elena; Calafell, Francesc; Comas, David
Abstract Basques show specific cultural, demographic, and genetic characteristics that have placed them as an isolated and unique population within Europe, such as their non-Indo-European language, Euskara. They have historically lived along the Western Pyrenees, between Spain and France, in one of the most important European glacial refugia during the Last Glacial Maximum. The most striking genetic characteristic is their highest frequency of the RhD blood group negative allele, a variant related to the hemolytic disease of the newborn. Both demographic and adaptive processes have been suggested as possible causes of the high frequency of RhD negative in Basques, but neither hypothesis has been clearly demonstrated. While previous studies on the Rh system in Basques have been mostly focused on serological and genotyping diversity, in this work we analyze genotyping and next generation sequencing data in order to provide a general framework of the genetic scenario of the system in Basques. In particular, we genotyped the most relevant variants of the system (D/d, E/e, and C/c), and sequenced three ~6 kb flanking regions surrounding the Rh genes in Basques and also in other populations for comparison. Our results are in agreement with previous studies, with Basques presenting the highest frequency of the RHD deletion (47.2%). Haplotype analyses of D/d, E/e, and C/c variants confirmed an association between the RhC allele, previously suggested to be under positive selection, and the RhD positive variant in non-sub-Saharan populations, including Basques. We also found extreme differentiation for the C/c variant when comparing sub-Saharan to non-sub-Saharan populations.